(untitled) (Journal of Human Sciences, 2026)
The current study aimed to identify the relative contribution of both positive thinking and emotional regulation in predicting psychological well-being among a sample of graduate students at the Libyan Academy - Ajdabiya branch, and to know the level of positive thinking and emotional regulation in predicting psychological well-being. The study also aimed to know the type of relationship between these the three variables The scales are the positive thinking scale prepared by Munshid (2013), the emotional regulation scale prepared by Aslim (2017), and the psychological well-being scale prepared by Carol Raiff (1989), which were applied to a sample of (180) male and female postgraduate students at the Libyan Academy - Branch. Ajdabiya, the study reached a set of results: The level of positive thinking and emotional regulation in predicting psychological well-being was high, with the arithmetic mean of positive thinking (175.88) and standard deviation (25.10),The arithmetic mean for emotional regulation is (77.85) and a standard deviation (9.68), and the arithmetic mean for psychological well-being is (174.25) and a standard deviation is (17.21). There is a strong statistically significant relationship between the study variables: psychological well-being, positive thinking, and emotional regulation. The value of the relationship was, respectively, positive thinking and emotional regulation (0.450**), precious well-being and positive thinking (0.850**), precious well-being and emotional regulation (0.820**). As for the relative contribution of both positive thinking and emotional regulation together (87%) in predicting psychological well-being, positive thinking and emotional regulation made statistically significant contributions to the variation in psychological well-being among postgraduate students at the Libyan Academy - Ajdabiya Branch.